1985
DOI: 10.1159/000124206
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Participation of the Neurohypophysial Hormones in the Hyperglucagonemic Response to Hemorrhage in the Rat

Abstract: Conscious adult male rats bearing jugular cannulae were injected with either normal rabbit serum (NRS) or with serum containing antibodies to both oxytocin (OT) and arginine vasopressin (AVP). In the NRS-treated group, plasma levels of OT, AVP and immunoreactive glucagon (IRG) were significantly elevated 10 min after hemorrhage (2.3 ml/100 g body weight over 5 min) whereas hyperglucagonemia was not detected in the antiserum-treated group until 30 min posthemorrhage. In animals which were deprived of water duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1986
1986
2005
2005

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…This is in accordance with previous findings, which showed that a 15 -30% acute reduction in blood volume increased AVP (9, 52 -54), and OT concentration in peripheral (5,50,55) and pituitary portal plasma (56), and increased AVP content and mRNA in the hypothalamus (52,57,58). The OT response to hemorrhage seems to be mediated via 5-HT 2 receptors, since the response was inhibited by pretreatment with the 5-HT 2Cþ2A antagonist LY.…”
Section: Discussionsupporting
confidence: 93%
“…This is in accordance with previous findings, which showed that a 15 -30% acute reduction in blood volume increased AVP (9, 52 -54), and OT concentration in peripheral (5,50,55) and pituitary portal plasma (56), and increased AVP content and mRNA in the hypothalamus (52,57,58). The OT response to hemorrhage seems to be mediated via 5-HT 2 receptors, since the response was inhibited by pretreatment with the 5-HT 2Cþ2A antagonist LY.…”
Section: Discussionsupporting
confidence: 93%
“…The characterization of this receptor at the molecular level in recent years has revealed that it is also abundantly expressed in the pancreas and that dDAVP, thought to be a selective V2 agonist, bound equally well to the V1b receptor [55]. Actually, a number of older studies have shown that vasopressin or dDAVP stimulates glucagon and insulin release in vivo, or in isolated perfused pancreas or in cultured cells from pancreatic origin [52, 56, 57, 58, 59]. It is thus conceivable that some of the effects observed in studies involving dDAVP administration may be due to an increase in glucagon-mediated direct and indirect effects on its main target organs, liver and kidney (fig.…”
Section: V1a and V1b Vasopressin Receptors In Diabetes Mellitusmentioning
confidence: 99%
“…Moreover, certain hypothalamic/pituitary peptides can influence both insulin and glucagon release. For example, vasopressin apparently potentiates the release of glucagon during hemorrhagic stress [45]. In addition, peptides released from islet cells may influence the secretions of other islet cell types in a paracrine manner.…”
Section: Criteria For Pancreatic Neuropeptidesmentioning
confidence: 99%